MANAJEMEN PERPUSTAKAAN MADRASAH BERBASIS KURIKULUM MERDEKA, TANTANGAN DAN STRATEGI - Sapari; Ima Rahmawati; Muhamad Robie Awaludin (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2026)
This article discusses the importance of madrasah library management in supporting the improvement of education quality in Indonesia, especially in the context of the Independent Curriculum. Based on Law Number 20 of 2003 concerning the National Education System, libraries are seen as crucial pillars for the holistic development of student potential. In the era of the Independent Curriculum, the role of madrasah libraries has transformed from merely a place to store books to a dynamic center of information and knowledge, functioning as a source of diverse literacy, an inclusive self-development space, and a strategic partner in character formation. Pancasila Student Profile, Case study at MTs Al-Falah Cibungbulang, Bogor, highlights the initial implementation of library management strategies in facing these challenges. This madrasah formulated a new vision for the library, rearranged the space, enriched the collection with limited funds and donations, and launched a simple literacy program assisted by KKN student volunteers. This study concludes that professional and adaptive library management is essential to support the vision of national education and the successful implementation of the Independent Curriculum.